1977
DOI: 10.1099/00221287-101-1-151
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Certain Assimilatory and Dissimilatory Enzymes during Bacterial Adaptation to Growth on Trimethylamine

Abstract: ~During the adaptation of Pseudumonas aminovorans from growth on succinate to growth on trimethylamine, the following enzymes were synthesized in the lag phase before exponential growth on trimethylamine began : trimethylamine and dimethylamine mono-oxygenases, trimethylamine-N-oxide aldolase (demethylase), glutathione-and NAD-dependent formaldehyde dehydrogenase, dye-linked formaldehyde dehydrogenase, hydroxypyruvate reductase and N-methylglutamate dehydrogenase. Differential plots suggested that the rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

1979
1979
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…However, the failure to detect any increase in activity during growth on C, compounds was more indicative of the enzyme having no role in the metabolism of C, compounds. This observation, although consistently found in the survey of organisms in this study, was in contrast to the initial report of Johnson & Quayle (1964) and also that of Boulton & Large (1977). The latter authors showed that when Pseudomonas aminovorans was transferred from a medium containing succinate as the carbon source to one containing trimethylamine certain enzymes associated with the metabolism of C, compounds were induced during the phase of adaptation by the bacteria to growth on the second substrate, Some of these enzymes, including the glutathione-and NAD+-dependent formaldehyde dehydrogenase, showed a rapid increase in specific enzyme activity, whilst others, including the dye-lin ked formaldehyde dehydrogenase, increased in specific activity only slowly.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, the failure to detect any increase in activity during growth on C, compounds was more indicative of the enzyme having no role in the metabolism of C, compounds. This observation, although consistently found in the survey of organisms in this study, was in contrast to the initial report of Johnson & Quayle (1964) and also that of Boulton & Large (1977). The latter authors showed that when Pseudomonas aminovorans was transferred from a medium containing succinate as the carbon source to one containing trimethylamine certain enzymes associated with the metabolism of C, compounds were induced during the phase of adaptation by the bacteria to growth on the second substrate, Some of these enzymes, including the glutathione-and NAD+-dependent formaldehyde dehydrogenase, showed a rapid increase in specific enzyme activity, whilst others, including the dye-lin ked formaldehyde dehydrogenase, increased in specific activity only slowly.…”
Section: Discussioncontrasting
confidence: 56%
“…Two of these enzymes are dye-linked, with the NH,+-independent enzyme having significantly low activity. A low activity for this enzyme has been reported by several workers (Johnson & Quayle, 1964;Boulton & Large, 1977;Bamforth & O'Connor, 1979). This could be a reflection of the true activity of the enzyme or a result of measuring the activity using non-physiological dyes as electron acceptors.…”
Section: Discussionmentioning
confidence: 98%
“…Microbial degradation of trimethylamine by aerobic bacteria (Colby and Zatman 1973;Boulton and Large 1977;Steenkamp and Mallinson 1976;Large and Haywood 1981;Levering et al 1981;Urakami et al 1990;Ohara et al 1990) and in laboratory-scale bioreactors (Partidário and Carrondo 1993;Lobo et al 1997) have been intensively studied. Although aerobic degradation is effective for the microbial removal of trimethylamine, molecular oxygen may not always be available in contaminated sites, possibly because of its prompt depletion by aerobic metabolism itself and its low solubility in water.…”
Section: Introductionmentioning
confidence: 99%
“…to their substrate specificity (Johnson & Quayle, 1964;Pate1 & Hoare, 1971;Boulton & Large, 1977). The FDH enzyme isolated from Methylococcus capsulatus (Bath) is particularly unusual in that it required a heat-stable (70 "C/12 min) dialysable protein for activity.…”
Section: S T a T E A N D H D A L T O Nmentioning
confidence: 99%